"What should happen before asymptomatic men decide whether or not to have a PSA test?" A report on three community juries. Issue 8 (19th October 2015) - Degeling, Chris; Rychetnik, Lucie; Pickles, Kristen; Thomas, Rae; Doust, Jennifer A; Gardiner, Robert A; Glasziou, Paul; Newson, Ainsley J; Carter, Stacy M
Abstract: Objectives: To elicit the views of well informed community members on the ethical obligations of general practitioners regarding prostate‐specific antigen (PSA) testing, and what should be required before a man undergoes a PSA test. Design and setting: Three community juries held at the University of Sydney over 6 months in 2014. Participants: Forty participants from New South Wales, of diverse social and cultural backgrounds and with no experience of prostate cancer, recruited through public advertising: two juries of mixed gender and ages; one all‐male jury of PSA screening age. Results: In contrast to Royal Australian College of General Practitioners guidelines, the three juries concluded that GPs should initiate discussions about PSA testing with asymptomatic men over 50 years of age. The mixed juries voted for GPs offering detailed information about all potential consequent benefits and harms before PSA testing, and favoured a cooling‐off period before undertaking the test. The all‐male jury recommended a staggered approach to providing information. They recommended that written information be available to those who wanted it, but eight of the 12 jurors thought that doctors should discuss the benefits and harms of biopsy and treatment only after a man had received an elevated PSA test result. Conclusions: Informed jury participants preferred that GPs actively supported individual men in making decisions about PSA testing, and that they allowed a cooling‐off period before testing. However, men of screening age argued that uncertain and detailed information should be communicated only after receiving an elevated PSA test result.